Pesticides, insecticides and male infertility - Roy, Priyanka; Phukan, Pranay Kumar; Changmai, Debojit; Boruah, Surajeet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pesticides, insecticides can damage the male reproductive system in a number of ways. They may cause reproductive toxicity with direct damage to the structure of the cells or as a result of biotransformation into metabolites. They can alter DNA structure. They may also act like hormones in the endocrine system and disrupt the function of the natural endogenous hormones, when doing so they are often called endocrine disrupting chemicals. The objective of the study was to evaluate the association of infertility with pesticide and insecticide exposure among the infertile male patients attending Out Patient Department of Assam Medical College and Hospital. Methods: The pesticides and insecticides used by the population were cypermethrin, thiaclopride, acetamiprid, emmacetin benzoate A total of 55 oligospermic infertile male patients were taken for the study. Twenty-seven among them were exposed to pesticides and rest twenty-eight unexposed cases were taken as control group. Semen analysis was done along with serum FSH, LH and Testosterone. Scrotal ultrasonography of the subjects was also done. One way ANOVA test and t-test assuming two unequal variances were applied to find out the statistical significance of the association of pesticides with their infertility. p<0.05 was taken to be significant. Results: A significant decrease in sperm concentration was found in the exposed group. Also, a significant increase in serum LH was found in the exposed group. A significant decrease in sperm concentration and serum testosterone along with a significant increase in serum FSH and LH was found with increase in duration of exposure to pesticides and insecticides. Conclusions: The gonadotoxic effect of pesticides and insecticides was reflected from the study and it was concluded that pesticide and insecticide exposure has got a definite relation with the infertility of the subjects evaluated in the study.